Notes muzyczny : połrocznik Wydziału Fortepianu, Organów, Klawesynu i Instrumentów Dawnych - Akademia Muzyczna Im. Grażyny i Kiejstuta Bacewiczów w Łodzi - Wydział Fortepianu, Organów, Klawesynu i Instrumentów Dawnych (2024)
"Notes Muzyczny" is an academic-art semi-annual publication, which has been published since 2014 by the Academy of Music in Łódź. It is issued in June and December. "Notes Muzyczny" is a journal that stands out among those published by music academies in Poland, offering the possibility to publish scientific articles related to various issues of classical and popular music - both to authors who are practicing musicians, as well as music theorists, musicologists and music therapists, and linguists, historians of art and literary scholars dealing with topics related to the musical arts. (Verlag)